Interaction between pheophorbide a and primary aliphatic amines. - Е. А. Larkina; A. L.A. Bui; E. P. Tkachevskaya; A. F. Mironov (Тонкие химические технологии)
The effect of primary aliphatic amine structure and conditions (solvent, the presence of tertiary amine) in course of its reaction with pheophorbide a and methylpheophorbide a on the yield of the final product – chlorine е6-13-alkylamide has been shown.